Field Evaluation of Conde Progenies with Early Heading Date and Resistance to Bacterial Leaf Blight - Fatimah, Fatimah; Prasetiyono, Joko; Dadang, Ahmad; Tasliah, Tasliah; Masumah, Masumah (Annales Bogorienses, 2019)
Heading date is one of key traits in rice adaptation to different environments. Rice with early maturity is very useful for increasing rice production extensively especially in Indonesia. The improvement of rice variety Conde for heading date and resistance to bacterial leaf blight (BLB) was developed through Marker Assisted Backcrossing approach (MAB). Xa7 derived from Conde as recipient parents for resistance to BLB and Hd2 gene derived from Nipponbare as a donor parent for heading date. The aim of this research was to evaluate the performance of heading date and agronomic traits of 85 BC2F4 lines in two field stations, Sukamandi (West Java) and Maros (South Sulawesi). Molecular analysis of Xa7 on chromosome 6 and Hd2 gene on chromosome 7 and agronomic performance was evaluated. Foreground analysis resulted 41% for Xa7 and 66.7% for Hd2 gene in homozygous condition. The majority of lines have similar heading date and yield with Conde and more resistance to bacterial leaf blight (BLB) than Conde. Six lines flowered earlier 5 days than Conde in Sukamandi and three lines flowered earlier 3 days in Maros. Twelve lines with flowered earlier than Conde, resistance to BLB and similar yield with Conde were selected for background analysis resulted 93% genome recovery. These lines would be further evaluated in preliminary yield trail for their stability.